2011
DOI: 10.1007/s10681-011-0609-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of endosperm development of allotriploid × diploid/tetraploid crosses in Lilium

Abstract: Lilium are Fritillaria-type plants. Triploid lilies, regardless of their male sterility, can be used as female parents to cross with appropriate males, in contrast to other triploid Polygonum-type plants, which are usually seedless. Up to now, however, little attention has been paid to the reason. Here we made allotriploid 9 diploid/tetraploid crosses in Lilium. Endosperm and progenies of LAA 9 AA/AAAA crosses were analyzed for ploidy level and genome composition. The endosperm of some LAA 9 AA/ AAAA ovules de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…Taken together, these data suggest that the chromosomal compositions of FDR gametes are more balanced than those of IMR gametes, resulting in FDR gametes being more viable and having a higher transmission rate than IMR gametes because of being suitable for selection as cultivars in nature. These findings are in accordance with Zhou et al 2008 studies 36. Indeed, since Lim et al (2001) discovered the IMR mechanism in LA interspecific hybrids 17, Barba-Gonzales (2005a) found that some F 1 OA hybrids produced 2n gametes via an IMR mechanism 20.…”
Section: Discussionsupporting
confidence: 85%
“…Taken together, these data suggest that the chromosomal compositions of FDR gametes are more balanced than those of IMR gametes, resulting in FDR gametes being more viable and having a higher transmission rate than IMR gametes because of being suitable for selection as cultivars in nature. These findings are in accordance with Zhou et al 2008 studies 36. Indeed, since Lim et al (2001) discovered the IMR mechanism in LA interspecific hybrids 17, Barba-Gonzales (2005a) found that some F 1 OA hybrids produced 2n gametes via an IMR mechanism 20.…”
Section: Discussionsupporting
confidence: 85%
“…Most conventional methodology is from 2x × 4x and 4x × 2x hybridization (Kesara 2003;Aleza et al 2010Aleza et al , 2012Moreno et al 2010;Zhou et al 2012;Ji et al 2013). Since 1996, the Plant Protection and Biotechnology Center of the Instituto Valenciano de Investigaciones Agrarias (IVIA, Moncada, Spain) has developed an extensive citrus triploid breeding program based on interploid sexual hybridizations.…”
Section: Artificial Hybridizationmentioning
confidence: 99%
“…The GISH has direct applications on the understanding of the genome evolution of polyploid hybrids, partial allopolyploids and recombinant inbred lines, as well as in detecting the amount of introgressed chromatin during the production of new lineages [11][12][13]. Therefore, the GISH has efficiently contributed for the analysis on the karyotypic stability of plant materials, indicating the best genotypes, and helping the assisted selection in different phases of crop improvement [9,14].…”
Section: Introductionmentioning
confidence: 99%